Are There Differences in Neurocognitive Function and Symptoms Between Male and Female Soccer Players After Concussions?. (December 2013) - Covassin, Tracey; Elbin, R.J.; Bleecker, Alisha; Lipchik, Adam; Kontos, Anthony P.
Background: Researchers have suggested that there are sex differences in outcomes after sport-related concussions. Factors such as sport type/rules, age, and body mass index (BMI) may influence these differences. Hypotheses/Purpose: The purposes of this study were (1) to examine neurocognitive performance after concussions between male and female soccer players and (2) to compare concussion symptoms between male and female soccer players. We hypothesized that female concussed soccer players would report more concussion symptoms and worse cognitive performance compared with male concussed soccer players. Study Design: Cohort study; Level of evidence, 2. Methods: A total of 39 male (mean BMI, 22.21 ± 2.34 kg/m 2 ; mean age, 17.69 ± 2.10 years) and 56 female (mean BMI, 23.47 ± 2.66 kg/m 2 ; mean age, 17.78 ± 2.30 years) concussed soccer players participated in this study. Participants were similar in age, history of concussion, sport, and time since injury. Participants completed computerized neurocognitive tests and symptom reports at baseline and 8 days after injury. Body mass index served as a covariate in all analyses. Results: After adjusting for BMI, results from a repeated-measures analysis of covariance (ANCOVA) revealed a group by time interaction for visual memory (F1, 82 = 5.50; P = .021). Specifically, female concussed soccer players (mean score, 68.7 ± 15.2) performed worse at 8 days after a concussion compared with male concussed athletes (mean score, 77.2 ± 8.9). Results of another ANCOVA for total concussion symptoms indicated an interaction for group by time (F1, 82 = 4.26; P = .04). Specifically, female concussed soccer players (mean score, 11.9 ± 15.7) reported more total concussion symptoms at 8 days compared with male concussed athletes (mean score, 5.3 ± 7.4). There were significant main effects for sex on verbal (F1, 82 = 5.98; P = .017) and visual (F1, 82 = 4.65; P = .034) memory, with female athletes reporting lower scores than male athletes. Female athletes also reported more symptoms on the migraine-cognitive-fatigue (F1, 82 = 10.8; P = .001) and sleep (F1, 82 = 9.2; P = .003) clusters than male athletes. Conclusion: In contrast to recent studies, after controlling for BMI, female athletes exhibited lower performance on visual memory composite scores and higher scores on total symptoms than male athletes after concussions.